Uncoupling protein gene UCP1-3826A/G, UCP2 Ins/Del and UCP3-55C/T polymorphisms in obese Turkish children - Verdi, Hasibe; Kınık, Sibel Tulgar; Baysan Çebi, H. Pınar; Yalçın, Yaprak Yılmaz; Yazıcı Güvercin, Ayşe Canan; Aydın, Beril; Tütüncü, Neslihan Başcıl; Ataç, F. Belgin (The Turkish Journal of Pediatrics, 2020)
Background. Mitochondrial uncoupling proteins (UCP) 1, 2 and 3 are members of the anion carrier protein family located in the inner mitochondrial membrane. There are various controversial reports on UCP genotypes and obesity in adults and children. This study aims to investigate the link between mostly studied UCP polymorphisms (UCP1-3826A/G, UCP2 Insertion/Deletion (Ins/Del) polymorphism of exon 8, and UCP3-55C/T Polymorphisms) and obesity in Turkish children. Furthermore, the relationships of UCP polymorphisms are also analyzed within the scope of metabolic parameters of obese children. Methods. Molecular screening of the UCP1, UCP2, and UCP3 gene polymorphisms was carried out in 189 children aged 6 to 18 years, 102 of who had exogenous obesity (54 girls) and 87 of whom were healthy controls (48 girls). In the obese group, fasting lipids, glucose and insulin levels were measured. In 60 obese children, an oral glucose tolerance test (OGTT) was performed with 0, 30, 60, 90 and 120 minutes of sampling for plasma glucose and insulin levels. Results. The frequency of UCP polymorphisms was similar in obese and non-obese children. In obese children, fasting lipids, glucose and insulin levels were not different among the UCP 1, 2 and 3 genotypes. While no relationship was found between the UCP 1 and 3 genotypes and glucose/insulin levels during OGTT, carriers of the Insertion allele with UCP2 Ins/Del polymorphism had significantly higher 30-minute insulin levels (p=0.018). Conclusions. Polymorphisms of the UCP1-3826A/G, UCP2 Ins/Del, and UCP3-55C/T are not associated with obesity and related pathologies in Turkish children. However, the presence of the Ins allele of the UCP2 gene has been found to have an unfavorable influence on early insulin excursion after glucose loading.
Keywords: OGTT; UCP; children; obese; polymorphism